Medication use risk management: hospital meets home care...reprinted from M. Aufseeser-Weiss and D. Ondeck, Medication use risk management: hospital meets home care, Home Health Care Management and Practice, [Vol. 12] No. 2, © 2000, Aspen Publishers, Inc. - Aufseeser-Weiss MR; Ondeck DA (Journal of Nursing Care Quality, 2001)
Risk management is an objective strategy that seeks to eliminate or decrease the chances of financial loss and legal action. Risk management focuses on an actual mistake, an accident, or a potential similar occurrence. Risks occur in nursing in a variety of practice settings. Nursing has identified several key areas in which systematic change has improved and decreased the risk factor encountered in practice. This article targets medication usage and administration and the methods introduced in quality improvement processes to decrease risks and potentially reduce financial and legal risk. Copyright © 2000 by Aspen Publishers, Inc.